C → T mutagenesis and γ-radiation sensitivity due to deficiency in the Smug1 and Ung DNA glycosylases - An, Qian (2005)
The most common genetic change in aerobic organisms is a C:G to T:A mutation. C → T transitions can arise through spontaneous hydrolytic deamination of cytosine to give a miscoding uracil residue. This is also a frequent DNA lesion induced by oxidative damage, through exposure to agents such as ionizing radiation, or from endogenous sources that are implicated in the aetiology of degenerative diseases, ageing and cancer. The Ung and Smug1 enzymes excise uracil from DNA to effect repair in mammalian cells, and gene-targeted Ung(−/−) mice exhibit a moderate increase in genome-wide spontaneous mutagenesis. Here, we report that stable siRNA-mediated silencing of Smug1 in mouse embryo fibroblasts also generates a mutator phenotype. However, an additive 10-fold increase in spontaneous C:G to T:A transitions in cells deficient in both Smug1 and Ung demonstrates that these enzymes have distinct and nonredundant roles in suppressing C → T mutability at non-CpG sites. Such cells are also hypersensitive to ionizing radiation, and reveal a role of Smug1 in the repair of lesions generated by oxidation of cytosine.